Price Risk Management by Futures Markets and Public Warehousing - Kozár, László; Fodor, Lóránt (Acta Agraria Debreceniensis, 2006)
The principal achievement of this paper is the combinative use of two market institutions: public warehousing and commodity exchange and how their joint application is beneficial for the players on the grain market. Based on a theoretical foundation, a calculation model was developed in order to assist short and long-term marketing decisions. It allows all the three participants of the market: producers, consumers and traders, to use this model in order to establish their own business strategy. The model can be used to analyse factors influencing the establishment of price; therefore, it can be also used for policy-making decisions.